Pemberdayaan Kelompok Budidaya Lebah Madu Melalui Pengembangan Edu-Ekowisata dan Virtual Maps Berbasis Ekonomi Hijau di Desa Sukamaju Kabupaten Ciamis - Ii Sujai; Marlina Nur Lestari; Tuti Rohayati; Refansyah Mukti (Universitas Muhammadiyah Sidenreng Rappang, 2025)
This community service program focuses on empowering the Kujang Kencana Honey Bee Cultivation Group in Sukamaju Village, Cihaurbeuti District, Ciamis Regency, through the development of edu-ecotourism and virtual maps based on the green economy concept. The program is motivated by the significant potential of the beekeeping sector as an environmentally friendly alternative source of income, as well as the opportunity to develop educational tourism in rural areas. The implementation methods include several stages: (1) training in institutional management and entrepreneurship; (2) mentoring in honey-based product innovation; (3) strengthening digital marketing capacity; and (4) developing digital technology-based virtual maps as media for promotion and tourism information. The results of this activity indicate improvements in the group members’ competencies in business management, product packaging, and information technology. Furthermore, the development of virtual maps has expanded promotional reach, improved tourist accessibility, and enhanced the appeal of environmentally based educational tourism. This program also fosters community awareness of the importance of sustainable green economic practices.